2014
DOI: 10.3390/ijms15059149
|View full text |Cite
|
Sign up to set email alerts
|

Functional Polymorphisms of the ABCG2 Gene Are Associated with Gout Disease in the Chinese Han Male Population

Abstract: BackgroundGout is a common type of arthritis that is characterized by hyperuricemia, tophi and joint inflammation. Genetic variations in the ABCG2 gene have been reported to influence serum uric acid levels and to participate in the pathogenesis of gout, but no further data have been reported in the Han Chinese population.MethodsPeripheral blood DNA was isolated from 352 male patients with gout and 350 gout-free normal male controls. High-resolution melting analysis and Sanger sequencing were performed to iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 34 publications
(44 reference statements)
4
37
1
Order By: Relevance
“…The results of our study was consistent with the GWAS on serum urate concentrations [13], we found that the TT genotype of rs2941484 in HNF4G gene was associated with hyperuricemia only in Chinese male population. Some case-control studies have previously identified gene variants that are associated with gender-specific susceptibility to hyperuricemia [31, 32], they both reported the gender-specific gene for hyperuricemia and gout in men rather than in women [33, 34]. The sex specificity demonstrated in the present study was not clear yet.…”
Section: Discussioncontrasting
confidence: 51%
“…The results of our study was consistent with the GWAS on serum urate concentrations [13], we found that the TT genotype of rs2941484 in HNF4G gene was associated with hyperuricemia only in Chinese male population. Some case-control studies have previously identified gene variants that are associated with gender-specific susceptibility to hyperuricemia [31, 32], they both reported the gender-specific gene for hyperuricemia and gout in men rather than in women [33, 34]. The sex specificity demonstrated in the present study was not clear yet.…”
Section: Discussioncontrasting
confidence: 51%
“…Many studies have found a strong connection between the Q126X polymorphism and increased risk of developing gout (Matsuo et al, 2009;Zhou et al, 2014;Li et al, 2015), with Matsuo et al (2009) showing a significant odds ratio of 5.97. This study also found the Q126X haplotype was present in up to 13.5% of gout patients in a Japanese population (Matsuo et al, 2009).…”
Section: Q126x (Rs72552713)mentioning
confidence: 99%
“…In the present study, the concentration of sUA, MO, �R, WBC, �LU, LDL�C, VLDL ��d T� w��� �d����fi�d �� b� ��g��fi����l� ��g��� �� ��� g��� �������� �������d w��� ����� in the healthy control subjects, which indicates that a close ����������� b��w��� �UA l�v�l� ��d g��� �x����. C������ ���d��� have demonstrated that genetic variation of ATP binding cassette subfamily G member 2 (ABCG2), solute carrier family 2 member 9 (SLC2A9), and solute carrier family 22 member 12 (SLC22A12) genes are involved in control of sUA levels, and the SNPs of ABCG2, SLC2A9 and SLC22A12 genes may increase the risk for an individual to develop gout (27)(28)(29). However, only ~10% of patients with hyperuricaemia would eventually develop gout (30) while the remaining 90% patients would not, which prompts investigation of the molecular basis involved in the metabolism and regulation of urate to further reveal the pathogenesis of gout.…”
Section: Discussionmentioning
confidence: 99%